2017
DOI: 10.1002/jmv.24794
|View full text |Cite
|
Sign up to set email alerts
|

Association of rhinovirus with exacerbations in young children affected by cystic fibrosis: Preliminary data

Abstract: Rhinovirus (RV) is a common respiratory viral infection linked to worsening of chronic respiratory diseases including cystic fibrosis (CF) and asthma. RV was tested by RT-PCR in samples (n = 465) collected from the upper (nasal swab, oropharyngeal suction, and sputum) and lower (bronchoalveolar washings) respiratory tract of 110 children with CF. Air samples (n = 52) collected from the operating theatres and outpatient clinics were tested for RV. RV was found in 43% of children <5 years suffering an exacerbati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 19 publications
2
7
0
Order By: Relevance
“…Our finding of human rhinovirus being the most commonly detected virus agrees with recent publications showing a high prevalence of HRV in early life, both in healthy children and those with CF [ [19] , [20] , [21] ]. Older studies commonly report RSV, influenza and adenovirus in the youngest populations, detected using immunofluorescence staining or virus isolated from tissue or respiratory secretions [ 8 , 9 ].…”
Section: Discussionsupporting
confidence: 92%
“…Our finding of human rhinovirus being the most commonly detected virus agrees with recent publications showing a high prevalence of HRV in early life, both in healthy children and those with CF [ [19] , [20] , [21] ]. Older studies commonly report RSV, influenza and adenovirus in the youngest populations, detected using immunofluorescence staining or virus isolated from tissue or respiratory secretions [ 8 , 9 ].…”
Section: Discussionsupporting
confidence: 92%
“…to epithelial cells as a possible mechanism to facilitate secondary bacterial infections [24]. Therefore our findings support the conclusions of previous studies that people with CF have high rates of RV infection, further implicating this virus as a potential major cause of respiratory illness in CF patients [3,9,13,14,25]. Preventing hospitalisation is a major goal for the management of chronic respiratory diseases, such as chronic obstructive pulmonary disease (COPD), asthma [26] and CF.…”
Section: Discussionsupporting
confidence: 89%
“…The most frequently detected respiratory virus in adults and children with CF was RV, however, RV was not detected more often in CF patients than in non-CF patients. Previous studies have also reported RV to be the most common cause of VRI in CF patients [9][10][11][12][13][14]22], possibly due to the upregulation of the cellular receptors for RV, ICAM-1 and LDL, in CF epithelial cells [23]. Moreover, RV infection can increase adherence of Staphylococcus spp.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Respiratory viruses have also been identified as triggers of exacerbations in other airway diseases such as cystic fibrosis 132,133 and bronchiectasis 134,135 and there is evidence of impaired antiviral immunity in these diseases. 136 Experimental infection studies may help to define the role of virus infection in these patient populations.…”
Section: Future Directions For Human Infection Modelsmentioning
confidence: 99%